Preventing job loss for people with Multiple Sclerosis - De Dios Perez, Blanca (2022)
Multiple Sclerosis (MS) is the most common chronic neurological condition affecting young adults. Many people are diagnosed with MS while they are of working age, and many leave the workplace prematurely. Vocational Rehabilitation (VR) aims to support those with illness or disability to find new employment, remain in or return to work (RTW). The effectiveness of VR for people with MS is inconclusive. This thesis aimed to develop, implement, and evaluate a job retention VR intervention for employed people with MS.